Constructing Moral Populism Through Narrative and Evaluation: A Linguistic Analysis of Dedi Mulyadi’s Digital Discourse in Indonesia - Nasution, Nazlah Syahaf; Kifli, Barli; Ayu, Fitri (Jurnal Sustainable, 2025)
This study examines how moral populism is linguistically constructed in the social media discourse of Indonesian public figure Dedi Mulyadi. Unlike dominant global models of populism that construct political legitimacy through conflict with elites, Mulyadi’s public persona emerges from empathetic encounters with ordinary citizens documented on YouTube. Rather than proposing policies, he performs ethical responsibility, framing poverty as moral virtue and leadership as personal caregiving. The analysis draws on twenty fully transcribed videos uploaded between January 2023 and January 2024 and applies an integrated linguistic framework combining discursive polarization, narrative, and appraisal theory. The findings show that (1) “the people” are constructed as morally deserving through narratives that romanticize hardship, (2) the leader is positioned as a cultural elder and ethical mediator rather than a political representative, and (3) indirect critiques of governance are articulated through linguistic contrasts between moral action and bureaucratic inaction. Public witnessing in the videos further legitimizes these moral acts, producing co-constructed authority. The study argues that Mulyadi’s discourse represents a non-antagonistic form of moral populism rooted in everyday care, shared cultural responsibility, and linguistic intimacy. These findings expand current scholarship by demonstrating how populist legitimacy in localized Southeast Asian contexts can emerge not through ideological opposition, but through ethical narration and interpersonal moral performance.